Will the real Moebius syndrome please stand up? A systematic review of the literature and statistical cluster analysis of clinical features. Issue 2 (17th December 2018) - Bell, Chris; Nevitt, Sarah; McKay, Victoria H.; Fattah, Adel Y.
Abstract : Moebius syndrome is a highly variable syndrome with abducens and facial nerve palsy as core features. Strict diagnostic criteria do not exist and the inconsistency of the associated features makes determination difficult. To determine what features are associated with Moebius syndrome we performed a systematic literature review resulting in a composite case series of 449 individuals labeled with Moebius syndrome. We applied minimum criteria (facial and abducens palsy) to determine the prevalence of associated clinical features in this series. Additionally, we performed statistical cluster analysis to determine which features tended to occur together. Our study comprises the largest series of patients with Moebius syndrome and the first to apply statistical methodology to elucidate clinical relationships. We present evidence for two groups within the Moebius diagnosis. Type 1: exhibiting micrognathia, limb anomalies and feeding/swallowing difficulty that tend to occur together. Type 2: phenotypically diverse but more associated with radiologically detectable neurologic abnormalities and developmental delay.